A Escola Nacional de Informações: a formação dos agentes para a inteligência durante o regime militar - Andrade, Fabiana de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The object of this research includes the training of information in Brazil during the military period, more specifically, since the inauguration of the National School of Informations ( NSI ) in 1972. The academic analysis of the School will seek to analyze a) the National Security Doctrin (USD) , developed by the National War College from its inception in 1958 , became the main doctrinal NSI substrate and b) to what extent it is possible to identify the incorporation of the National Security Doctrine in the education of information agents. For this, we analyzed the regional, national and international contexts of thIS time, as well as a comparison between the concepts established by the USD and the instructions given in the manuals, handouts and summaries of classes NSI was established. Thus, to understand the main aspects of the National Security Doctrine and its presence as a major doctrinal basis of the National Information School, will be possible to establish an analysis that is capable of indicating the manner in which the precepts have been adapted and adopted in the formation of intelligence officers formed at the National School of Informations - ESNI

O objeto desta pesquisa compreende a formação dos agentes de informações no Brasil durante o período militar, mais especificamente, a partir da inauguração da Escola Nacional de Informações (EsNI), em 1972. A análise curricular da Escola permitiu verificar a) se a Doutrina de Segurança Nacional, desenvolvida pela Escola Superior de Guerra, a partir de sua criação em 1958, foi o principal substrato doutrinário da EsNI e; b) em que medida é possível identificar a incorporação da Doutrina de Segurança Nacional na educação dos agentes de informações. Para tanto, foram analisadas as conjunturas regionais, nacionais e internacionais da época, assim como estabelecida uma comparação entre os conceitos estabelecidos pela DSN e as instruções presentes nos manuais, apostilas e sínteses de aulas da EsNI. Desta forma, ao compreendermos os principais aspectos da Doutrina de Segurança Nacional, bem como sua presença como base doutrinária principal da Escola Nacional de Informações, foi possível estabelecer uma análise capaz de indicar a maneira pela qual os preceitos desta foram adaptados e adotados na formação dos agentes de informações formados pela Escola Nacional de Informações –EsNI
Keywords: História; Segurança nacional - História; Informações (segurança nacional); Serviço militar; História militar; Brasil - Historia - 1964-1985; History